2014
DOI: 10.1016/j.toxicon.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Larval pufferfish protected by maternal tetrodotoxin

Abstract: Marine pufferfish contain tetrodotoxin (TTX), an extremely potent neurotoxin. All species of the genus Takifugu accumulate TTX in the liver and ovaries, although the tissue(s) in which it is localized can differ among species. TTX is the major defense strategy the pufferfish appears to use against predators. TTX is also used as a male-attracting pheromone during spawning. Here we demonstrate an additional (and unexpected) use of maternal TTX in the early larval stages of the Takifugu pufferfish. Predation expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 19 publications
3
55
0
1
Order By: Relevance
“…was isolated from the ovary of pufferfish T. obscures as a symbiotic microbe in our previous study (Yang et al, 2010). Plasmid pNe-1 encoding TTX biosynthesis enzymes to produce TTX may confer a selective advantage on the host Aeromonas in colonizing pufferfish, because TTX is the major defense strategy the pufferfish appears to use against predators and it also used as a male-attracting pheromone during spawning (Fuhrman, 1986;Itoi et al, 2014;Matsumura, 1995). However, in in vitro culture of Aeromonas, cells containing plasmid pNe-1 will not own a selective advantage; on the contrary, the plasmid will be an energy drain due to production of TTX.…”
Section: Discussionmentioning
confidence: 99%
“…was isolated from the ovary of pufferfish T. obscures as a symbiotic microbe in our previous study (Yang et al, 2010). Plasmid pNe-1 encoding TTX biosynthesis enzymes to produce TTX may confer a selective advantage on the host Aeromonas in colonizing pufferfish, because TTX is the major defense strategy the pufferfish appears to use against predators and it also used as a male-attracting pheromone during spawning (Fuhrman, 1986;Itoi et al, 2014;Matsumura, 1995). However, in in vitro culture of Aeromonas, cells containing plasmid pNe-1 will not own a selective advantage; on the contrary, the plasmid will be an energy drain due to production of TTX.…”
Section: Discussionmentioning
confidence: 99%
“…In pufferfish, the toxin that accumulates in the eggs is transferred to the hatched larvae, where it is maintained for a certain period after hatching (Nagashima et al 2010). Itoi et al (2014) observed juveniles of generally nontoxic fish that ingest pufferfish (T. niphobles and T. rubripes) larvae and then promptly spit them out, and presumed that the TTX transferred from the mother works to repel predators, based on the findings that TTX was primarily localized on the body surface of the larvae and that rainbow trout (Oncorhynchus mykiss) and arctic char (Salvelinus alpinus) are able to sense extremely low levels of TTX with gustatory receptors (Yamamori et al 1988). Flatworms, ribbon worms, and horseshoe crabs also possess high concentrations of TTX in their eggs (Miyazawa and Noguchi 2001;Noguchi and Arakawa 2008), and TTX may act as a repellant, thereby contributing to the survival of the eggs and hatched larvae, like in pufferfish.…”
Section: -1 Defense Against Predatorsmentioning
confidence: 99%
“…47 This toxin inhibits voltage-dependent sodium channels, thereby interfering with the propagation of the action potential. This toxin has been used in neuroscience to identify specific neural circuits in different animal models.…”
Section: Zebrafish and Mycotoxin Studiesmentioning
confidence: 99%